Implementing Faith-Building Principles in Whistleblowing Systems to Combat Corruption - Sujiantoro, Hibertus; Refangga, Galih Setyo; Mustika, Ulfa Dyah; Firmanto, Bayu; Doloksaribu, Tio Arriela (Yayasan Ilomata, 2025)
This research investigates the implementation of faith-building principles within the utilisation of whistleblowing systems to combat corrupt behaviour. Employing a descriptive research design, this study concludes that the whistleblowing system at MAN 2 Malang serves not only to maintain organisational integrity and ethics but also to cultivate an environment fostering openness and accountability. The Bina Iman (Faith Building) principle, emphasising honesty, responsibility, and social concern, provides a crucial foundation for encouraging the active participation of teachers and students in reporting deviant or detrimental actions. A well-implemented whistleblowing system establishes a secure and anonymous communication channel, mitigating the fear of retaliation. By integrating Bina Iman values, MAN 2 Malang reinforces the reporting mechanism and builds a culture that champions transparency. This study reveals that direct involvement of all stakeholders in the reporting process can enhance awareness of corrupt behaviour and promote stronger preventive measures. Evaluation of existing mechanisms and practices underscores the importance of ethics and integrity education and training, which the Bina Iman doctrine aims to achieve and internalise. The research concludes that applying Bina Iman principles not only strengthens the whistleblowing system but can also act as a catalyst for change, bringing corruption to light and reducing its prevalence at MAN 2 Malang. Through the synergy of spiritual principles and administrative practices, this educational institution can serve as a model for other institutions in effectively combating corruption based on high moral values.